2011
DOI: 10.2215/cjn.05440610
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Relationship between Mycophenolate Mofetil Dose and Mycophenolic Acid Exposure

Abstract: SummaryBackground and objectives Mycophenolate mofetil (MMF) is an immunosuppressive drug used in renal transplant patients. Upon oral administration it is hydrolyzed to the active agent mycophenolic acid (MPA). In renal transplant recipients, MMF therapy is optimal when the area under the curve of MPA is 30 to 60 mg⅐h/L. When MMF doses are adjusted, a linear relationship between dose and MPA exposure is assumed. In this study, the linearity of MMF pharmacokinetics was investigated.Design, setting, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 28 publications
5
59
0
Order By: Relevance
“…In line with a recent observation in adult transplant patients [42], we observed a non-linear relationship between individual MPA exposure (AUC) and dose (Figure, Supplemental Digital Content 3, http://links.lww.com/TDM/A21). Based on recursive partitioning, we therefore stratified patients into high or low dosing groups based on BSA-normalized dose and subsequently explored the genetic effects on normalized pharmacokinetic parameter estimates.…”
Section: Discussionsupporting
confidence: 90%
“…In line with a recent observation in adult transplant patients [42], we observed a non-linear relationship between individual MPA exposure (AUC) and dose (Figure, Supplemental Digital Content 3, http://links.lww.com/TDM/A21). Based on recursive partitioning, we therefore stratified patients into high or low dosing groups based on BSA-normalized dose and subsequently explored the genetic effects on normalized pharmacokinetic parameter estimates.…”
Section: Discussionsupporting
confidence: 90%
“…It is supported by less than expected increase in MPA exposure with increasing MMF doses. 15 MPA is extensively bound to albumin (97%-99%) in patients with normal renal and liver function. However, the MPA binding can be decreased by several factors, including hypoalbuminemia, uremia, elevated concentrations of the MPA primary metabolite, 7-O-MPA-glucuronide, which competes for albuminbinding sites, and hyperbilirubinemia.…”
Section: Therapeutic Drug Monitoring Of Mycophenolic Acid In Lupus Nementioning
confidence: 99%
“…In an early study, the authors compared MMF of 1000 mg with MMF of 1500 mg, both two times daily, in cyclosporine-treated patients, and found MPA AUC and MMF dose presented a linear relationship 18 . However, de Winter et al 6 reported that the bioavailability decreased with increasing MMF doses. The authors found the relative bioavailability was 176%, 133%, 85% and 76% in patients treated with MMF doses of 250, 500, 1500 and 2000 mg in combination with tacrolimus, compared with an MMF dose of 1000 mg (100%).…”
Section: Discussionmentioning
confidence: 99%